2018
DOI: 10.1128/jvi.00331-18
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Properties of Normal Human Keratinocytes Determine Transformation Responses to Human Papillomavirus 16 DNA

Abstract: Human papillomavirus (HPV) infection of the genital tract is common; however, only about 10 to 15% of infections persist, and approximately 10 to 15% of these persistent infections result in cancer. Basal epidermal stem cells are the presumed target cells for HPV infection, providing a reservoir of latently infected cells that persist over time and initiate lesions. However, it is not known whether stem cell density has any influence on transformation of human keratinocytes by HPV. We explored the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…High-risk HPVs have been proposed to infect stem cells (65, 66). A recent study showed that HPV16 preferentially transforms basal keratinocytes with stem cell properties (67) and that the HPV E7 oncoprotein, which inhibits Rb similarly to MCV LT, activates pluripotency genes, including Oct4, Sox2, and Nanog (68). Thus, the targeting of cellular reprogramming factors, such as Sox2 and Oct4, may be a common mechanism for stem cell transformation by tumor viruses.…”
Section: Discussionmentioning
confidence: 99%
“…High-risk HPVs have been proposed to infect stem cells (65, 66). A recent study showed that HPV16 preferentially transforms basal keratinocytes with stem cell properties (67) and that the HPV E7 oncoprotein, which inhibits Rb similarly to MCV LT, activates pluripotency genes, including Oct4, Sox2, and Nanog (68). Thus, the targeting of cellular reprogramming factors, such as Sox2 and Oct4, may be a common mechanism for stem cell transformation by tumor viruses.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the virus by itself induces an immunomodulation as previously demonstrated for other viruses (37, 38). Notably, we identified the reservoir of HPV in non-neoplastic epithelial cells within the crypts of colonic normal mucosa adjacent to the neoplastic mucosa and we demonstrated that these cells were stem-cells, which are known to be susceptible to transformation by HPV 16 (39, 40). It can be argued that following inflammatory response to a number of stimuli (also including dysbiosis) (41), non-cancer stem cells may be activated into cancer stem cells, sustaining a feed-forward circuit of self-renewal, proliferation, differentiation and neoplastic transformation in a condition of immune evasion, as previously demonstrated (40, 4244).…”
Section: Discussionmentioning
confidence: 94%
“…NHKc were isolated from neonatal foreskin as previously described ( Akerman et al, 2001 ) and cultured according to Woappi et al ( Woappi et al, 2018 ). Briefly, KSFM media (Thermo Fisher Scientific Waltham, MA) was supplemented with 1% PenStrep/10 mg/ml gentamycine, 50 μg/mL bovine pituitary extract, 20 ng/ml EGF, 10 ng/ml basic fibroblast growth factor, 0.4% bovine serum albumin (BSA), and 4 μg/ml insulin.…”
Section: Methodsmentioning
confidence: 99%